PENGARUH KOMPETENSI DOSEN DAN LINGKUNGAN KAMPUS TERHADAP KEPUASAN MAHASISWA S1 AKUNTANSI UNIVERSITAS PAMULANG - Prima Sadewa; Riska Damayanti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The aims of this study are (1) to determine the effect of lecturer competence on student satisfaction, (2) to determine the effect of the campus environment on student satisfaction, and (3) to determine the effect of lecturer competence and the campus environment together on student satisfaction. This research is a research that uses a quantitative approach. Furthermore, this research is a type of associative research. The data collection technique is in the form of a questionnaire. The data analysis methods in this study are data quality test, classical assumption test, regression test and hypothesis testing. The results in this study are as follows: (1) there is an influence of lecturer competence on student satisfaction, (2) there is an influence of academic services on student satisfaction, (3) there is an effect of lecturer competence and campus environment simultaneously on student satisfaction.